PENGARUH TEORI FRAUD PENTAGON DAN EFIKASI DIRI TERHADAP KECURANGAN AKADEMIK MAHASISWA PADA PEMBELAJARAN DARING (Studi Kasus Pada Mahasiswa Akuntansi Di Kota Malang) - Erina Sasmita Arjuni; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study was conducted to analyze how the influence of the influence of Pentagon Fraud Theory and Self-Efficacy on Student Academic Fraud in Online Learning. The case study in this research is accounting students in Malang City. The number of samples that can be used in this study were 213 respondents who met the sample criteria. In this study using multiple regression analysis method. The results of this study are simultaneously the variables of pressure, opportunity, rationalization, competence, arrogance and self-efficacy simultaneously have a significant effect on academic cheating. While partially 1) The pressure variable partially has a significant and positive effect on academic cheating, 2) The opportunity variable partially has a significant and positive effect on academic cheating. 3) The rationalization variable partially has a significant and positive effect on academic cheating, 4) The competence variable partially has a significant and positive effect on academic cheating, 5) The arrogance variable partially has a significant and negative effect on academic cheating, 6) The self-efficacy variable partially does not significant and negative effect on academic cheating.Keywords: pressure, opportunity, rationalization, competence, arrogance, self-efficacy, academic cheating.